Nutritional Status and the Associated Factors in Under Five Years Children of Lamjung, Gorkha and Tanahun Districts of Nepal - Dhungana, Govinda Prasad (Nepalese Journal of Statistics, 2017)
Background: The nutritional status of children is important as it determines their health, physical growth as well as development, productive life and academic performance. The national figures for stunting, underweight and wasting in under five years children in Nepal stands at 41%, 29% and 11%, respectively according to NDHS 2011. However, the magnitude of this problem in hilly areas of Nepal is not well understood. Objectives: The objective of this study was to find the nutritional status of 6 to 59 months of children and its associated factors. Materials and Methods: A cross-sectional, population-based study design has been used for this study. The study population was 6 to 59 months children who were permanent or temporary residents of the study area. The respondent was the mother of the under 5 year child. A total 10% (n=1353) study participants were selected from each of the 4 VDCs of Lamjung and Gorkha, and each of the 5 VDCs of Tanahun during April-May, 2014 by applying systematic random sampling. A semi-structured questionnaire was administered to mothers by face to face interview method. The anthropometric measurements (weight and height) were also recorded. Binary logistic regression was applied to identify the factors associated to the nutritional status. Results: In the study, 56.3% were boys and 43.7% were girls. The prevalence of wasting, stunting and underweight was 10.6% (95% C.I: 9.0-12.2), 53.9% (95% C.I: 51.2-56.6) and 20.8% (95% C.I: 18.6-23.0), respectively. The wasting, stunting and underweight were higher in boys than in girls. The factors were duration of breast feeding, occupation of mothers, family size, site of delivery, height of mothers and age of mother during the delivery. Conclusion: Stunting was more prevalent than wasting in the study districts and implies that there is a problem of chronic malnutrition. The factors highlighted in this study should be adequately addressed by concerned authorities to address malnutrition in these hilly districts of Nepal. Nepalese Journal of Statistics, 2017, Vol. 1, 15-28